Financial inclusion and stability in Ethiopia using bank-level data: A two-step system GMM estimation [version 2; peer review: 1 approved, 2 approved with reservations] - Andualem Mekonnen; Filmon Hando; Mohammed Arebo (F1000Research)
Background This paper examines the impact of FI on bank stability within Ethiopian context, using panel data from 17 commercial banks over the period 2015-2023. Given the scarcity of research focused on the relationship between FI and bank stability in Ethiopia, this paper seeks to address a crucial gap by analyzing both conventional and digital aspects of FI in relation with bank stability. Methods A two-stage principal component analysis (PCA) was conducted to construct a composite FI index, integrating 10 conventional and 5 digital indicators. The study applied a two-step robust system generalized method of moments (GMM) to analyze the effects of FI on bank stability, tests nonlinearities using Lind and Mehlum’s (2010) U-test, and examines causality through Dumitrescu-Hurlin (2012) and Juodis et al. (2021) causality tests. Results The result reveals an inverted U-shaped relationship between FI and bank stability. FI enhances stability up to a 30.3% threshold, beyond which increased transaction costs, information asymmetries, and adverse selection risks weaken stability. Capital adequacy moderates this effect, raising the threshold to 35.1%, but its stabilizing role diminishes at higher levels. Granger causality tests confirm a bidirectional relationship. Additionally, bank efficiency and GDP growth enhance stability, while real interest rates, total assets, and income diversification exert destabilizing effects. Conclusions This study makes three key contributions. First, it provides the first empirical analysis of the FI-stability nexus in Ethiopia. Second: (i), it develops a multidimensional FI index; (ii), explores both linear and nonlinear relationships, and (iii) examines macroprudential regulation as a moderating factor. Third, it tests causality, offering policy insights. To enhance stability while mitigating risks, policymakers must balance FI expansion, enforce regulatory frameworks, and implement targeted capital requirements. Regulators should strengthen consumer protection and financial literacy, while banks must optimize outreach, manage credit risk, and ensure prudent asset allocation and liquidity management to sustain financial stability.